Mitigasi Struktural Berbasis 3D Google SketchUp Pada Sekolah Muhammadiyah Rawan Tanah Longsor di Kabupaten Karanganyar - Muhammad Rizal Pahleviannur; Muhammad Hafidhudin Anwar; Salma Lutfiani Sochiba; Angga Yuda Prasetyo; Jumar Febrianto; Abdul Aziiz Rayh Gilang (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This research purposes to knowing the expediency level from the physic structure condition building of Muhammadiyah schools in Karanganyar toward disaster combination through three dimension Google SketchUp. The research design used in this study is descriptive quantitative methods. Quantitative data collected by research instrumental of inquiry observation by questionare. Making SketchUp based of observation and square measuring. The result of this research is indicate the expediency of schools building focused on SD IT Jumapolo have reached 77.19% and SD Muhammadiyah Jatiyoso by reached 51.41%. So, SD Muhammadiyah Jatiyoso must be more respected for structural mitigation disaster participation.